Suppression of Fcγ-Receptor-Mediated Antibody Effector Function during Persistent Viral Infection - Yamada, Douglas H. (Immunity, 2015)
Understanding how viruses subvert host immunity and persist is essential for developing strategies to eliminate infection. T cell exhaustion during chronic viral infection is well described, but effects on antibody-mediated effector activity are unclear. Herein, we show that increased amounts of immune complexes generated in mice persistently infected with lymphocytic choriomeningitis virus (LCMV) suppressed multiple Fcγ-receptor (FcγR) functions. The high amounts of immune complexes suppressed antibody-mediated cell depletion, therapeutic antibody-killing of LCMV infected cells, and human CD20-expressing tumors, as well as reduced immune complex-mediated cross-presentation to T cells. Suppression of FcγR activity was not due to inhibitory FcγRs or high concentrations of free antibody, and proper FcγR functions were restored when persistently infected mice specifically lacked immune complexes. Thus, we identify a mechanism of immunosuppression during viral persistence with implications for understanding effective antibody activity aimed at pathogen control.